Biomarker research for Henoch-Schönlein purpura nephritis based on “omics” techniques - Zhou, Xuejiao; Yuan, Zhengwei; Jiang, Hongkun; Ju, Yaoyao; Chen, Cheng; Zhang, Wenjie; Liu, Huining; Zhang, Liqing; Qi, Meixia; An, Dong (Frontiers in Medicine, 2025)
Henoch-Schönlein purpura (HSP) is a common autoimmune disease in children. The lesions primarily involve small vessels in the skin, kidneys, joints and intestines. Henoch-Schönlein purpura nephritis (HSPN) caused by HSP is the main factor affecting the prognosis and outcome of the disease, and severe cases may develop into end-stage renal insufficiency. Renal biopsy serves as the primary diagnostic tool for HSPN, but it is an invasive test with poor reproducibility. Which is not conducive to clinical promotion. The discovery of new biomarkers using traditional laboratory testing methods and omics techniques provide new possibilities for HSPN to discover additional biomarkers, such as genomics, transcriptomics, proteomics, metabolomics and epigenomics. These technologies offer benefits such as high throughput, high sensitivity, and reduced need for biological fluid samples, which are expected to make greater contributions to the screening of promising biomarkers for purpuric nephritis. The current article reviews recent advances in omics-based research on potential biomarkers in samples from different sources of HSPN, including blood, urine, kidney tissue, and associated cells, which may provide a foundation for early diagnosis, prognosis, and treatment of HSPN.